Analisis Tingkat Kepuasan dan Kepentingan Pengguna Aplikasi SAKTI dengan PIECES Framework - Heru Pudyo Nugroho; Jamila Lestyowati (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2020)
This study aims to analyze the level of satisfaction and importance of Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) users, the strengths and weaknesses of SAKTI, and the components that need to be improved. The study used descriptive quantitative methods with primary data from 45 respondents. They are SAKTI users from the piloting office units in regional offices of DJP in Central Java and Yogyakarta. The data analysis method is the Importance Performance Analysis (IPA) method in the evaluation of SAKTI information systems with PIECES framework consisting of six attributes, namely Performance, Information, Economy, Control, Efficiency, and Service. The results showed that all PIECES variables of level of importance are very important. All PIECES attributes have a negative gap value. It means that the satisfaction value is below their expectations. Based on the IPA analysis, it was found that there were 12 PIECES items in quadrant A as the main priority for improvement.